1984
DOI: 10.1093/oxfordjournals.jbchem.a134879
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of N-Long Chain Acyl Aminoacylase from Pseudomonas diminuta

Abstract: N-Long chain acyl aminoacylase II (Enzyme II) catalyzing the hydrolysis of N-long chain acyl amino acids was purified about 2,000-fold from the cell extracts of Pseudomonas diminuta with 1.8% of activity yield. The purified enzyme was homogeneous on polyacrylamide gel electrophoresis and the molecular weight was 220,000. Enzyme II differed from N-long chain acyl aminoacylase I (Enzyme I) in molecular weight, in substrate specificity, and in behavior toward temperature and pH. Enzyme II showed broader substrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…However, the enzyme does not show any activity toward N -acetyl- l -amino acids, indicating that the enzyme is classified as a type of long chain acyl aminoacylase. Aminoacylases showing such a wide substrate specificity have not been reported to date ( ). Furthermore, the enzyme shows deacylation activity toward N -lauroyl- l -dipeptides, although it has no peptidase activity.…”
Section: Resultsmentioning
confidence: 99%
“…However, the enzyme does not show any activity toward N -acetyl- l -amino acids, indicating that the enzyme is classified as a type of long chain acyl aminoacylase. Aminoacylases showing such a wide substrate specificity have not been reported to date ( ). Furthermore, the enzyme shows deacylation activity toward N -lauroyl- l -dipeptides, although it has no peptidase activity.…”
Section: Resultsmentioning
confidence: 99%
“…First, studies have reported the isolation of bacterial N-acyl amino acids from cultured environmental isolates, yet the enzymatic origins of these metabolites were not described (26,33,41). Second, microbial enzymes that either hydrolytically degrade or fur-ther modify long-chain N-acyl amino acids have been recognized for many years (5,15,21,31). Third, E. coli-based heterologous expression of related N-acylhomoserine lactone synthases and lyso-ornithine lipid synthases (OlsB homologs) results in the accumulation of only the corresponding natively produced metabolites (16,39).…”
Section: Discussionmentioning
confidence: 99%